On a question of A. N. Skiba about totally saturated formations - Safonov, V.G. (Algebra and Discrete Mathematics, 2008)
It is proved that the lattice of τ-closed totally saturated formations of finite groups is distributive. This is a solution of Question 4.2.15 proposed by A. N. Skiba in his monograph "Algebra of Formations" (1997).